2012
DOI: 10.5194/hess-16-1647-2012
|View full text |Cite
|
Sign up to set email alerts
|

Meta-analysis of the effects of soil properties, site factors and experimental conditions on solute transport

Abstract: Abstract. Preferential flow is a widespread phenomenon that is known to strongly affect solute transport in soil, but our understanding and knowledge is still poor of the site factors and soil properties that promote it. To investigate these relationships, we assembled a database from the peer-reviewed literature containing information on 733 breakthrough curve experiments under steady-state flow conditions. Most of the collected experiments (585 of the 733 datasets) had been conducted on undisturbed soil colu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

9
58
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(67 citation statements)
references
References 112 publications
(59 reference statements)
9
58
0
Order By: Relevance
“…A positive relationship between bulk density and preferential transport in undisturbed soil columns has been found in several studies due to the presence of well‐aligned and connected cracks typical of soils with high clay content (Norgaard et al, 2013; Poulsen et al, 2006). After reviewing 580 experiments from the literature, Koestel et al (2012) found a clay content threshold of 8% for preferential flow in undisturbed columns. The clay content in our study field exceeded that threshold but was almost constant and we did not find any relationship with the preferential flow parameters.…”
Section: Resultsmentioning
confidence: 99%
“…A positive relationship between bulk density and preferential transport in undisturbed soil columns has been found in several studies due to the presence of well‐aligned and connected cracks typical of soils with high clay content (Norgaard et al, 2013; Poulsen et al, 2006). After reviewing 580 experiments from the literature, Koestel et al (2012) found a clay content threshold of 8% for preferential flow in undisturbed columns. The clay content in our study field exceeded that threshold but was almost constant and we did not find any relationship with the preferential flow parameters.…”
Section: Resultsmentioning
confidence: 99%
“…The solute spread is sometimes also described as the dispersivity or, in model‐independent studies, as the apparent dispersivity (Vanderborght et al, ). Two recent comprehensive metastudies on dispersivities have been published by Vanderborght and Vereecken (, n = 635) and Koestel et al (, n = 733). These studies have demonstrated that the dispersivity is positively correlated with the lateral and longitudinal scale of the experiment, the flow rate, and the clay content and negatively with the sand content, and the geometric mean particle size (Koestel et al, ).…”
Section: Ptfs In Earth System Sciencesmentioning
confidence: 99%
“…Two recent comprehensive metastudies on dispersivities have been published by Vanderborght and Vereecken (, n = 635) and Koestel et al (, n = 733). These studies have demonstrated that the dispersivity is positively correlated with the lateral and longitudinal scale of the experiment, the flow rate, and the clay content and negatively with the sand content, and the geometric mean particle size (Koestel et al, ). It is likewise known from the same study that dispersivities are smaller for repacked than for undisturbed soil by 1 order of magnitude.…”
Section: Ptfs In Earth System Sciencesmentioning
confidence: 99%
“…Thus, molecular diffusion in the bulk solution and tortuosity of the porous medium () are important determinants of D. Koestel et al [21] reported a positive correlation between water flux rate (q) and D from large number of studies. In addition, the solute dispersion scales with the first power of velocity of water in capillary tubes [22].…”
Section: Resultsmentioning
confidence: 99%